Gromov - Hausdorff Dimension and Measure of Separable Metric Spaces - Morawo, Monsuru A.; D., Hina A.; Y., Azeez K. (Asian Journal of Science, Technology, Engineering, and Art, 2025)
In this paper, we proved that dimension of Gromov – Hausdorff hyperspace of Riemannian manifold depends on the cardinality of measurable Riemannian manifold.